Gejala Kesenjangan antara Ideologi dan Pragmatisme Pembangunan Ekonomi Masyarakat Pedesaan - Tri Pranadji (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2002)
EnglishFor the last three decades, critics and discourse on concept or ideology regarding rural economic development is extremely weak. The aim of this paper is to give evidences of systematically failure of the said rural economic development. The basis of the failure is the unclear ideology used as the framework of rural economic development. The